Proton therapy for pediatric diencephalic tumors - Grippin, Adam J.; McGovern, Susan L. (Frontiers in Oncology, 2023)
Diencephalic tumors tend to be low grade tumors located near several critical structures, including the optic nerves, optic chiasm, pituitary, hypothalamus, Circle of Willis, and hippocampi. In children, damage to these structures can impact physical and cognitive development over time. Thus, the goal of radiotherapy is to maximize long term survival while minimizing late effects, including endocrine disruption leading to precocious puberty, height loss, hypogonadotropic hypogonadism, and primary amenorrhea; visual disruption including blindness; and vascular damage resulting in cerebral vasculopathy. Compared to photon therapy, proton therapy offers the potential to decrease unnecessary dose to these critical structures while maintaining adequate dose to the tumor. In this article, we review the acute and chronic toxicities associated with radiation for pediatric diencephalic tumors, focusing on the use of proton therapy to minimize treatment-related morbidity. Emerging strategies to further reduce radiation dose to critical structures will also be considered.